Mapping socioeconomic vulnerability to hydrological risk in Italy - the case of Emilia - Romagna - Huber, Franziska (2023)
This paper investigates the interplay between flood hazard and social vulnerability in Italy's Emilia Romagna region. It conducts an in-depth, municipal-level analysis to construct a social vulnerability index, highlighting how each socio-economic factor contributes to it. By conducting a correlation analysis and employing Geographic Information Systems (GIS), the study not only maps the spatial variability of social vulnerability but, by integrating these findings with flood hazard maps, it creates a comprehensive social vulnerability exposure map. This research highlights the critical role of social vulnerability assessments in shaping effective flood risk mitigation policies and provides valuable insights for policymakers for their decision-making.